Correcting the disconnect between phylogenetics and biodiversity informatics - Miller, Joseph T.; Jolley-Rogers, Garry (Zootaxa, 2014)
Rich collections of biodiversity data are now synthesized in publically available databases and phylogenetic knowledge now provides a sound understanding of the origin of organisms and their place in the tree of life. However, these knowledge bases are poorly linked, leading to underutilization or worse, an incorrect understanding of biodiversity because there is poor evolutionary context. We address this problem by integrating biodiversity information aggregated from many sources onto phylogenetic trees. PhyloJIVE connects biodiversity and phylogeny knowledge bases by providing an integrated evolutionary view of biodiversity data which in turn can improve biodiversity research and the conservation decision making process. Biodiversity science must assert the centrality of evolution to provide effective data to counteract global change and biodiversity loss.